Simplification of educational texts on technical disciplines as a method of didactic reduction - Nemchenkova, S.; Shmatkov, D/ (Problems of Engineer-Pedagogical Education, 2018)
On the basis of the conducted theoretical research main types of a text simplification, and also the manual, automated and automatic technicians of application of a method are systematized. It is defined that application of the considered method of a didactic reduction is caused by continuous growth of theoretical and empirical data on disciplines of the corresponding direction. It is revealed that methods of determination of texts complexity as well as simplification technicians are directed to the general cases and generally don't consider specifics of technical texts – existence of symbolical designations, definition and/or transformation of number of variables in formulas, different types of communications in charts, columns, schemes etc. Revealed a possibility of application of a didactic reduction method for technical disciplines that provide of adaptation to specifics of the corresponding technical subject domain which consist in development of analysis algorithms of formulas, schemes, tables, schedules, counts,hodographs and other types of illustrative material which occurs in technical texts. It is also revealed an urgent need for adaptation of simplification method to the texts submitted in the Ukrainian language.